An Integrated Care Model With Implementation Roadmap to Improve Chlamydia trachomatis Management and Control in India - Pierre P. M. Thomas; Ramesh R. Allam; Elena Ambrosino; Jelena Malogajski; Jonathan A. Lal; Servaas A. Morré; Servaas A. Morré; Servaas A. Morré; Remco P. H. Peters; Remco P. H. Peters (Frontiers Media S.A., 2018)
Chlamydia trachomatis is the world's most prevalent bacterial Sexually Transmitted infection (STI). It is associated with a wide range of health consequences and sequelae in both the short and long term. Enhanced control of urogenital C. trachomatis infection is particularly important in low- and middle-income countries such as India, where most of the burden goes unnoticed and where limited systematic data is available to gauge the current situation. The World Health Organization (WHO) recently issued its latest strategy on STIs, which is aligned with the achievement of the Sustainable Development Goals (SDGs). Taking the WHO framework into account; this paper puts forward an integrated care model to strengthen the management and control of C. trachomatis in India. The model is compiled of five key components of STI management (awareness, prevention diagnosis, treatment and follow-up). The model considers barriers to effective C. trachomatis control into account. The barriers are discussed and compiled into different categories. A roadmap for the implementation of other similar models to enhance C. trachomatis control in the future is provided.